2020
DOI: 10.21203/rs.3.rs-79416/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Could Graph Neural Networks Learn Better Molecular Representation for Drug Discovery? A Comparison Study of Descriptor-based and Graph-based Models

Abstract: Graph neural networks (GNN) has been considered as an attractive modelling method for molecular property prediction, and numerous studies have shown that GNN could yield more promising results than traditional descriptor-based methods. In this study, based on 11 public datasets covering various property endpoints, the predictive capacity and computational efficiency of the prediction models developed by eight machine learning (ML) algorithms, including four descriptor-based models (SVM, XGBoost, RF and DNN) an… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…To benchmark the deep model, two popular machine learning methods, 8 , 33 RF and SVM, were implemented with scikit-learn. The two methods were trained on the same training sets for the binary classification but taking a single compound as input using either the ECFP6 fingerprints or the tokenized SMILES strings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To benchmark the deep model, two popular machine learning methods, 8 , 33 RF and SVM, were implemented with scikit-learn. The two methods were trained on the same training sets for the binary classification but taking a single compound as input using either the ECFP6 fingerprints or the tokenized SMILES strings.…”
Section: Resultsmentioning
confidence: 99%
“…Both RF and SVM prove to consistently perform well on a variety of tasks. 8 , 33 For the RF, the number of trees was set to 100, and no maximum depth for the tree was specified. The Gini Index for information gain was used.…”
Section: Methodsmentioning
confidence: 99%
“…This falls in line with earlier research of ours [12] , and is not uncommon to occur. For example, Jiang and colleagues [34] showed that the Attention FP [35] , a graph neural network providing state of the art results on many benchmark sets, performs only on par with descriptor-based models. The results of the GCN can be found in the Supplementary Information .…”
Section: Resultsmentioning
confidence: 99%
“…These results come at a time when graph-based neural networks are increasingly popular for computational chemistry, although their benefits have also come into question (29). The performance of the de facto standard 2,048 bit Morgan fingerprint can be improved simply by using pharmacophoric atom invariants and/or larger fingerprint sizes.…”
Section: Discussionmentioning
confidence: 99%